Los dilemas para consumir justicia: algunos alcances de la tutela procesal del consumidor en la vía administrativa y el arbitraje de consumo - Rejanovinschi Talledo, Moisés (2015)
This paper argues that the consumer should choose the procedural mechanism that satisfies their need to resolve a dispute and being compensated. Also, the administration, in order to defend rights of consumers, must have the authority to prefer the Constitution through diffuse constitutional control.